PENGARUH FRAUD PENTAGON TERHADAP TAX AVOIDANCE - Siti Mundiroh; Fitria Eka Ningsih (Politeknik Raflesia Press, 2022)
This study aims to determine the effect of Pentagon Fraud on Tax Avoidance. The type of research conducted is descriptive quantitative research with secondary data sources in the form of annual reports and the population of the Food and Beverages sub-sector manufacturing companies listed on the IDX for the 2016-2020 period. The data in this study were processed using Microsoft excel and Eviews 12. The number of samples in this study were 14 companies with 5 years of observation so that 70 observation data were obtained. The sampling technique used in this research is purposive sampling where the sample is taken based on certain criteria. The data analysis technique in this research uses panel data model test, descriptive statistics, classical assumption test, model accuracy test (coefficient of determination), and hypothesis testing, namely simultaneous test or F test and partial test, namely t test. The results of this study indicate that simultaneously all independent variables have an effect on Tax Avoidance. However, partially only the External Pressure variable has an effect on Tax Avoidance. Meanwhile, Arrogance, Competence, Financial Target, Ineffective Monitoring and Razionalization variables have no effect on Tax Avoidance.